Международные новости архитектуры - Grigorieva, Anna (проект байкал, 2019)
The news section presents the Baku Declaration adopted during the 43rd session of the UNESCO World Heritage Committee and announces the results of Architectural Competition “Projet Loi 130”, as well as the results of the Architectural Design Competition for the Knowledge and Innovation Center in Tripoli, Lebanon.